Bibliometric Analysis of Research Trends in Islamic Multiculturalism: Evidence from the Scopus Database - Lismawati; M. Arifin Rahmanto; Siti Nurhalimatussadiyah (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to examine the intellectual structure and research trends of Islamic multiculturalism published in the Scopus database between 1991 and 2024 through a comprehensive bibliometric analysis. Theoretical framework: The study is grounded in the theoretical framework of multiculturalism, intercultural dialogue, and knowledge mapping, which explains how scholarly networks, thematic evolution, and citation patterns shape the development of academic knowledge. Literature review: Previous studies have extensively discussed Islamic multiculturalism from theological, educational, and sociopolitical perspectives. However, few investigations have systematically mapped the global scientific landscape, influential contributors, institutional collaboration, and thematic evolution of this field using bibliometric techniques, leaving an important gap in understanding its intellectual development. Method: This study employs a quantitative bibliometric approach by analyzing 223 Scopus-indexed publications using VOSviewer and RStudio. The analysis covers publication growth, authorship patterns, institutional productivity, country contributions, citation performance, co-occurrence of keywords, and thematic visualization through network, overlay, and density analyses. Results: The findings indicate a consistent increase in scholarly interest, with publication peaks recorded in 2014, 2019, and 2021, although a slight decline occurred in recent years. Modood T. emerged as the most productive author, while Universiti Kebangsaan Malaysia, the University of Bristol, and Swinburne University of Technology were identified as the leading institutions. The United Kingdom, the United States, and Australia dominated research productivity. Keyword mapping demonstrates that multiculturalism, Islam, and religion constitute the principal research clusters, whereas overlay visualization reveals an evolution from studies emphasizing Islam and multiculturalism toward broader discussions of religion and social diversity. Citation analysis identifies Mepschen (2010) as the most globally cited publication and Niyozov (2009) as the most influential locally cited work. Implications: The findings imply that future studies should expand interdisciplinary collaboration and investigate underexplored themes, including cultural anthropology, liberalism, diversity education, and social inclusion. Novelty: The novelty of this study lies in providing a comprehensive bibliometric mapping that integrates publication performance, intellectual structure, thematic evolution, and research gaps, offering a strategic reference for future scholarship and policy development in Islamic multiculturalism.